Supplementation with galacto-oligosaccharides in early life persistently facilitates the microbial colonization of the rumen and promotes growth of preweaning Holstein dairy calves - Meinan Chang; Feifei Wang; Fengtao Ma; Yuhang Jin; Peng Sun (Animal Nutrition, 2022)
We aimed to determine the effects of dietary supplementation with galacto-oligosaccharides (GOS) on the growth performance, serum parameters, and the rumen microbial colonization and fermentation of pre-weaning dairy calves. The study comprised 2 phases of 28 and 42 d, respectively. During phase 1, 24 newborn female Holstein dairy calves were randomly allocated to consume a diet supplemented with 10 g/d GOS (GOS, n = 12) or not (CON, n = 12). Thereafter, during phase 2, the GOS group was further divided into 2 groups: one that continued to consume GOS (GOSC, n = 6) and one that no longer consumed GOS (GOSS, n = 6), alongside the CON group. Galacto-oligosaccharides increased the average daily gain (ADG), body weight, feed efficiency, and serum high-density lipoprotein-cholesterol concentration of dairy calves during phase 1 (P < 0.05). Supplementation with GOS for the entire study reduced the incidence of diarrhea and increased the serum total protein and Ca concentrations (P < 0.05) compared with the CON group. The effect of GOS supplementation persisted after it was stopped because the ADG and final body weight of the GOSS group were higher than those of the CON group (P < 0.05). Furthermore, the GOSS group showed a persistently lower incidence of diarrhea and greater colonization of the rumen with probiotics, at the expense of less beneficial bacteria, which would promote ruminal fermentation and microbial protein synthesis. These findings provide a theoretical basis for the rational application of prebiotics and have important practical implications for the design of early life dietary interventions in dairy calf rearing.